A review of land consolidation in the state of Uttar Pradesh, India: Qualitative approach. (January 2020) - Munnangi, Aswani Kumar; Lohani, Bharat; Misra, Subhas Chandra
Highlights: Uttar Pradesh is the only state in India where land consolidation (LC) is underway since 1954. Qualitative approach is employed to understand the holistic view of LC in greater depth. The complete LC process in the state is implemented manually until now. In order to get over the challenges linked to manual LC implementation, the study emphasises on the ways to improve it. The study acts as an anchor to the development of a comprehensive system for LC. Abstract: Land consolidation (LC) is the most important and ignored land reform in India. It aims to consolidate fragmented agricultural landholdings into fewer and larger units. Uttar Pradesh (UP) is the only state in the country that is currently implementing it. Currently, 4497 villages in the state are under consolidation process. This paper explores LC activities in UP, their contribution to sustainable development goals (SDGs), and limitations of the current approach. The study also has technological and policy suggestions to make LC more effective. The qualitative data collected for analysis are LC documents, interviews and direct observations in 14 villages, six tehsil headquarters, three district headquarters, and Consolidation Directorate between 2013–2018. As all actives of LC are executed manually involving large amounts of data, long project duration are common along with the possibilities of committing mistakes in the decision-making process. Technological suggestions proposed are to use advanced mapping technique for cadastral survey, build an information system for handling data, develop tools to automate different LC activities by integrating artificial intelligence with GIS, and examine challenges and success factors for technological adoption. This study contributes and acts as a base to future research aimed to improve, ease and expedite LC activities in UP.